Determinants of Cloud Accounting Software Adoption: Evidence from Accounting Firms in Bangkok - อินเสือ อังคณา; อุ้ยศิริพร จิดาภา; จันทร์อิทธิกุล ณัฏฐนิช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to (1) examine factors influencing the adoption of cloud accounting software among accounting firms in Bangkok, (2) assess the relative importance of each factor, and (3) determine the influence of factors on decision-making regarding the use of online accounting programs. The sample consisted of 340 registered quality accounting firms in Bangkok, selected via Simple Random Sampling. Data were collected using online questionnaires validated for content validity (IOC ≥ 0.6) and internal consistency (Cronbach’s Alpha ≥ 0.70). Descriptive statistics and multiple regression analysis were employed for data analysis. The results revealed that all five factors significantly influenced the adoption of cloud accounting software (p < 0.05). Ranked by standardized regression coefficients (Beta) from highest to lowest: (1) security, (2) program functionality, (3) after-sales service, (4) capability, and (5) price. The model yielded R² = 0.62 and Adjusted R² = 0.61, indicating that these five factors explained 61% of the variance in cloud accounting software adoption.